Randomized controlled trial of text message reminders for increasing influenza vaccination - Regan, Annette; Bloomfield, L.; Peters, I.; Effler, P. (2017)
© 2017, Annals of Family Medicine, Inc. All rights reserved. PURPOSE Seasonal influenza vaccine is recommended and funded for groups at higher risk of serious infection, but uptake is suboptimal. We conducted a randomized controlled trial of short message service (SMS) reminders for influenza vaccination. METHODS Six weeks after seasonal influenza vaccinations began, we identified high-risk patients who had a mobile telephone number on record at 10 practices in Western Australia. Thirty-two percent of the selected patients had already been vaccinated in the current year and were ineligible. Of the remaining 12,354 eligible patients at each practice one-half were randomly assigned to receive a vaccination reminder by SMS (intervention) and the rest received no SMS (con-trol). Approximately 3 months after the SMS was sent (the study period), vaccination data were extracted from the patients’ electronic medical records. Log-bino-mial regression models were used to calculate the relative risk (RR) of vaccination between the intervention and control group. RESULTS Twelve-percent (769 of 6,177) of the intervention group and 9% (548 of 6,177) of the control group were vaccinated during the study period, a 39% relative increase attributable to the SMS (RR = 1.39; 95% CI, 1.26-1.54). For every 29 SMSs sent, costing $3.48, 1 additional high-risk patient was immunized. The greatest effect was observed for children younger than 5 years, whose parents were more than twice as likely to have their child vaccinated if they received a SMS reminder (RR = 2.43; 95% CI, 1.79-3.29). CONCLUSION We found S MS reminders to be a modestly effective, low-cost means to increase seasonal influenza vaccine coverage among high-risk patients.